Assessment of the competitiveness of the economies of the EAEU countries - Kosherbayeva, Aigul; Kylbayev, Erlan; Sautbekov, Daulet (Public Administration and Civil Service, 2022)
The article presents the results of a study of competitiveness as a factor in the development of the EAEU member states since the creation of the integration association in 2015 and 2020. The study is based on data from EAEU statistics. The article assesses the competitiveness of the economies of the EAEU countries on the basis of indicators of foreign and mutual trade, the share of the manufacturing industry in the total volume of industrial production, as well as labor productivity. According to the results of the analysis, the countries were identified - those that receive a greater effect from participation in the integration union, and those who are more focused on trade with third countries. Using the author's methodology, an assessment of the competitiveness of industry was carried out and an index of export similarity was calculated in comparison with the European Union. The results showed that the complementarity of economies within the EAEU is still low, and therefore the contribution of integration processes to the development of the economy is still insignificant. The main reasons for the current state of affairs, in addition to the factor of low complementarity of the structure of the economies of the EAEU countries, are that the advantages associated with the creation of the EAEU require the implementation of national economic policy measures related to supporting promising areas of cross-border interregional cooperation.